Case Report: Regenerative hepatic pseudotumor induced by tislelizumab in a lung cancer patient - Wang, Wenrui; Li, Wei; Zhang, Tianqi; Jin, Zhenjing; Yang, Lanlan (Frontiers in Immunology, 2025)
Immune checkpoint inhibitors (ICIs) have revolutionized the treatment for different types of cancers, providing significant clinical benefits. However, these therapies are associated with various immune-related adverse events (irAEs), including hepatic manifestations such as hepatitis, sinusoidal obstruction syndrome (SOS), and nodular regenerative hyperplasia. Among these, regenerative hepatic pseudotumors (RHPs) are exceptionally rare and poorly described in literature. Here, we report the case of a 66-year-old man with metastatic non-small-cell lung cancer (NSCLC) who developed a hepatic pseudotumor during routine imaging following treatment with the anti-programmed cell death 1 (PD-1) therapy, tislelizumab. Despite the presence of a hepatic lesion on imaging, the patient exhibited no clinical symptoms or biochemical evidence of severe immune-mediated hepatitis. Following cessation of anti-PD-1 therapy and initiation of systemic steroid therapy, the hepatic pseudotumors stabilized without further growth. The findings suggest that ICI therapy may be associated with the development of regenerative hepatic pseudotumor (RHP). Given the nonspecific and potentially misleading imaging features of RHP, biopsy is essential for accurate diagnosis and differentiation from malignant lesions such as hepatic metastases. Early histological evaluation through biopsy can prevent unnecessary interventions and guide appropriate management in patients presenting with liver lesions during or after ICI therapy. This case suggests a possible association between the development of RHP and tislelizumab treatment. The effect of ICI-induced hepatic pseudotumors on NSCLC progression is unclear and requires further investigation.